Differing abundance changes in birds and butterflies in boreal agricultural landscapes - Arkkila, Sarella; Bosco, Laura; Heliölä, Janne; Kuussaari, Mikko; Lehikoinen, Aleksi; Piha, Markus; Seimola, Tuomas; Tiainen, Juha; Ekroos, Johan (Springer Nature, 2026)
Biodiversity is declining at an alarming rate, particularly in agricultural landscapes. Long-term monitoring data indicate that farmland birds and butterflies have declined, yet we lack an understanding of potential drivers of abundance change of these indicator taxa over space and time. Here, we studied abundance changes of birds and butterflies in Finnish farmlands from 2001 to 2023 at local and regional scales, sampled in the same study locations and regions. Additionally, we analysed if the abundance change is correlated between the two groups (taxa) at a site-level, and if changes in abundance over time can be attributed to comparable ecological, species-specific traits, reflecting variation in species temperature index, body size, and habitat breadth. We found that butterflies significantly declined in their abundance, which was not the case for birds. Additionally, abundance changes between geographical regions differed for both taxa, indicating that similar regional drivers are affecting species of both taxa. Species-specific traits did not explain varying abundance changes of both taxa. These results indicate that abundance changes are driven by taxon- and species-specific factors, rather than by more broadly comparable, ecological characteristics. Our results highlight the importance of utilising several different indicator species, representing different taxonomic groups, when assessing the implications of agricultural practices on biodiversity.
Keywords: biodiversity loss; farmland birds; climate change; land-use change; insect decline; agroecosystems